2007
DOI: 10.1021/jp067212o
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Kinetics and Thermochemistry of the Forward and Reverse Reaction Cl + C6H6 = HCl + C6H5

Abstract: The laser flash photolysis resonance fluorescence technique was used to monitor atomic Cl kinetics. Loss of Cl following photolysis of CCl 4 and NaCl was used to determine k(Cl + C 6 H 6 ) ) 6.4 × 10 -12 exp(-18.1 kJ mol -1 /RT) cm 3 molecule -1 s -1 over 578-922 K and k(Cl + C 6 D 6 ) ) 6.2 × 10 -12 exp(-22.8 kJ mol -1 /RT) cm 3 molecule -1 s -1 over 635-922 K. Inclusion of literature data at room temperature leads to a recommendation of k(Cl + C 6 H 6 ) ) 6.1 × 10 -11 exp(-31.6 kJ mol -1 /RT) cm 3 molecule -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…[43][44][45][46] The photochemical reactor is a stainless steel six-way cross heated within an oven. Gas temperatures T in the reaction zone, where the arms of the reactor (i.d. )…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[43][44][45][46] The photochemical reactor is a stainless steel six-way cross heated within an oven. Gas temperatures T in the reaction zone, where the arms of the reactor (i.d. )…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Sokolov et al observed no formation of HCl and set an upper limit of k1 < 2.5 x 10 -16 cm 3 molecule -1 s -1 , which agrees with extrapolation of our data. We may also compare k1 with our previous measurements of the analogous reaction 4 [10]. The latter is faster by about a factor of 3 at 700 K and a factor of 2 at 1000 K.…”
Section: Discussionmentioning
confidence: 52%
“…In these distillations the middle 80% was trapped at 77 K. Details of the apparatus have been given elsewhere [7,10]. Briefly, atomic Cl is formed by pulsed laser photolysis of a small fraction of chlorobenzene at 193 nm.…”
Section: Methodsmentioning
confidence: 99%
“…4. The theoretical 0 K reaction enthalpies, combined with H 298 -H 0 values either from the literature [25,27] or computed here (17.9 kJ mol À1 for C 6 H 5 I), yield D r H 298 = À204 and À15 kJ mol À1 for channels (1b) and (1c), respectively. These values are in reasonable agreement with the experimental data given above.…”
Section: Discussionmentioning
confidence: 62%
“…The invariance of our k 1 data with s res suggests that little dissociation in fact occurred, in part because the initially cold gas flow does not spend all of s res at the temperature of the reaction zone. Any C 6 H 5 produced will be rapidly consumed by reaction with C 6 H 5 I, with a rate constant of about 2 Â 10 À11 cm 3 molecule À1 s À1 [25]. At 900 K and with a typical [C 6 H 5 I] = 4 Â 10 13 molecule cm À3 , a steady state concentration of around 1.5 Â 10 10 molecule cm À3 would be attained, which is too small to perturb the [H] profiles.…”
Section: Resultsmentioning
confidence: 99%